Long-Term Health-Related Quality of Life in Survivors of Congenital Diaphragmatic Hernia - Derraugh, Gabrielle; Lum Min, Suyin A.; Keijzer, Richard (European Journal of Pediatric Surgery, 2020)
The health-related quality of life (HRQoL) of survivors of congenital diaphragmatic hernia (CDH) is presently unknown. Literature prior to 2015 suggests that CDH survivors have worse HRQoL compared with the general population. However, due to changes in the diagnosis, management, and follow-up of CDH patients, this may no longer be true. The objective of this review was to determine what recent literature suggests regarding the HRQoL of CDH survivors. We reviewed all studies published between April 9, 2015, and April 6, 2020, that described the HRQoL of CDH survivors. Studies were identified using PubMed, and the references of the identified papers were searched for additional studies eligible for inclusion. Seven studies describing HRQoL in CDH survivors using validated measures of HRQoL for children, PedsQL (Pediatric Quality of Life Inventory), KIDSCREEN-52, and Comprehensive Quality of Life Scale – School Version were examined. The findings were disparate. One study suggested that CDH survivors had better than average HRQoL scores, three studies found patients and controls had equivalent scores, and two studies reported poor outcomes for CDH patients. The final study found no effect of disease severity on HRQoL, as determined by prenatal ultrasound. Evidence published between 2015 and 2020 suggests that CDH patients have an HRQoL equivalent to the general population.
Keywords: congenital diaphragmatic hernia; quality of life; health-related quality of life; long-term outcomes; pediatric surgery